Besnoitia besnoiti infection alters both endogenous cholesterol de novo synthesis and exogenous LDL uptake in host endothelial cells - Silva, Liliana M. R. (Sci Rep, 2019)
Besnoitia besnoiti, an apicomplexan parasite of cattle being considered as emergent in Europe, replicates fast in host endothelial cells during acute infection and is in considerable need for energy, lipids and other building blocks for offspring formation. Apicomplexa are generally considered as defective in cholesterol synthesis and have to scavenge cholesterol from their host cells for successful replication. Therefore, we here analysed the influence of B. besnoiti on host cellular endogenous cholesterol synthesis and on sterol uptake from exogenous sources. GC-MS-based profiling of cholesterol-related sterols revealed enhanced cholesterol synthesis rates in B. besnoiti-infected cells. Accordingly, lovastatin and zaragozic acid treatments diminished tachyzoite production.  Moreover, increased lipid droplet contents and enhanced cholesterol esterification was detected and inhibition of the latter significantly blocked parasite proliferation. Furthermore, artificial increase of host cellular lipid droplet disposability boosted parasite proliferation. Interestingly, lectin-like oxidized low density lipoprotein receptor 1 expression was upregulated in infected endothelial hostcells, whilst low density lipoproteins (LDL) receptor was not affected by parasite infection. However, exogenous supplementations with non-modified and acetylated LDL both boosted B. besnoiti proliferation. Overall, current data show that B. besnoiti simultaneously exploits both, endogenous cholesterol biosynthesis and cholesterol uptake from exogenous sources, during asexual replication.